Alopecia as surrogate marker for chemotherapy response in patients with primary epithelial ovarian cancer: A metaanalysis of four prospective randomised phase III trials with 5114 patients. Issue 7 (May 2015) - Sehouli, Jalid; Fotopoulou, Christina; Erol, Edibe; Richter, Rolf; Reuss, Alexander; Mahner, Sven; Lauraine, Eric Pujade; Kristensen, Gunnar; Herrstedt, Jörn; du Bois, Andreas; Pfisterer, Jacobus
Abstract Purpose Alopecia is a common side-effect of chemotherapy and affects quality of life of cancer patients. Some patients and physicians believe that alopecia could be a surrogate marker for response to chemotherapy and impact on prognosis. However, this was never been tested in a sufficiently large cohort of ovarian cancer patients. Patients and methods We analysed retrospectively the meta-databank of four prospective randomised phase-III-trials with platinum- and taxane-based 1st-line-chemotherapy in patients with advanced epithelial ovarian cancer (EOC) regarding the impact of alopecia overall outcome. Results For 4705 (92.0%) of a total of 5114 EOC-patients alopecia was documented. They had received on median six cycle platinum-taxane chemotherapy (range 0–11) with 4186 (89.0%) having completed ⩾6 cycles. Worst alopecia grade was 0 in 2.4%, 1 in 2.9% and 2 in 94.7% of the patients. In a univariate analysis, including all patients, grade-0/1 alopecia was associated with significantly lower progression free survival (PFS) and overall survival (OS) compared to grade-2 alopecia. However when assessing only those patients who completed ⩾6 chemotherapy-cycles and hence eliminating the bias of lower total dose of treatment, alopecia failed to retain any significant impact on survival in the multivariate analysis. Merely the time point of alopecia onset was an independent prognostic factor of survival: patients who developed grade-2 alopecia up to cycle 3 had a significantly longer OS compared to patients who experienced alopecia later during therapy (hazard ratio (HR): 1.25; 95% confidence interval (CI): 1.04–1.50). Conclusions Within a large EOC-patient cohort with 1st-line platinum- and taxane-based chemotherapy early onset alopecia appears to be significantly associated with a more favourable outcome in those patients who completed ⩾6 chemotherapy cycles. It remains to be elucidated if early onset alopecia is just a surrogate marker for higher sensitivity to chemotherapy or if other biological effects are underlying.